2020
DOI: 10.1167/jov.20.8.17
|View full text |Cite
|
Sign up to set email alerts
|

Test–retest of a phoria adaptation stimulus-induced functional MRI experiment

Abstract: This study was designed to identify the neural substrates activated during a phoria adaptation task using functional magnetic resonance imaging (MRI) in young adults with normal binocular vision and to test the repeatability of the fMRI measurements for this protocol. The phoria adaptation task consisted of a block protocol of 90 seconds of near visual crossed fixation followed by 90 seconds of far visual uncrossed fixation, repeated three times; the data were collected during two different experimental sessio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 87 publications
0
9
0
Order By: Relevance
“…The MNI coordinate of the most significant T value was extracted and a 5 mm radius sphere consisting of 81 voxels was created around this peak voxel coordinate using the MarsBaR MATLAB toolbox as part of SPM 77 . Our prior studies showed that the 5 mm radius sphere produced the highest intraclass correlation coefficients within our repeatability studies 67 , 68 and has been used in a prior oculomotor fMRI investigation 78 . Additionally, the mean beta weights from 3 and 7 mm radius spheres consisting of 19 and 179 voxels, respectively were also computed for comparison to the 5 mm radius sphere results.…”
Section: Methodsmentioning
confidence: 60%
See 3 more Smart Citations
“…The MNI coordinate of the most significant T value was extracted and a 5 mm radius sphere consisting of 81 voxels was created around this peak voxel coordinate using the MarsBaR MATLAB toolbox as part of SPM 77 . Our prior studies showed that the 5 mm radius sphere produced the highest intraclass correlation coefficients within our repeatability studies 67 , 68 and has been used in a prior oculomotor fMRI investigation 78 . Additionally, the mean beta weights from 3 and 7 mm radius spheres consisting of 19 and 179 voxels, respectively were also computed for comparison to the 5 mm radius sphere results.…”
Section: Methodsmentioning
confidence: 60%
“…The fast and slow fusional vergence systems were studied using functional imaging employing established methods published by our group using these exact protocols 67 , 68 . The visual stimuli are different compared to the behavioral studied performed in the laboratory because of the physical constraints of the magnet.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Functional magnetic resonance imaging (fMRI) has been used to assess cortical activity associated with convergence. 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 However, prior research has not investigated the neural substrates associated with convergence eye movements using fMRI under conditions where the stimulus to vergence is varied such that one vergence subtype is primarily expected to change. For example, previous studies have employed light‐emitting diodes (LEDs) placed at different distances as vergence stimuli.…”
Section: Introductionmentioning
confidence: 99%